Rancang Bangun Purwarupa Mobil Bergerak Menggunakan Pengendali Suara Berbasis Mikrokontroler Atmega328 - Serli Yuni Wulandari; Joko Saputro; Asruddin Asruddin (Sistem Komputer & Teknologi Intelegensi Artifisial (SIKOMTIA), 2023)
One type of prototype car with interesting special abilities to develop is a voice-controlled prototype car based on the ATmega328 microcontroller module EasyVR, Motor Driver as the stepper motor controller, and using wheels with a stepper motor as the driver. EasyVR Commander serves as the voice recorder. In the control system, several voice commands are used. The first command is "ROBOT", waiting for the LED to light up, and then the second command is "FORWARD", which makes the prototype car move forward. The first command is "ROBOT", waiting for the LED to light up, and then the second command is "REVERSE", which makes the prototype car move backward. The first command is "ROBOT", waiting for the LED to light up, and then the second command is "RIGHT", which makes the prototype car move to the right. The first command is "ROBOT", waiting for the LED to light up, and then the second command is "LEFT", which makes the prototype car move to the left. The first command is "ROBOT", waiting for the LED to light up, and then the second command is "ACTION", which triggers a reaction from the prototype car. The prototype car will move according to voice commands and pressure through sound waves.